Clinical outcomes in hypertension patients after coronary stenting due to exertional angina - R. N. Akhtereyev; A. S. Galyavich; L. V. Baleeva; Z. M. Galeeva (Российский кардиологический журнал, 2020)
Aim. To study clinical outcomes in hypertension patients after coronary stenting due to exertional angina.Material and methods. The study included 214 patients with class 3 stable angina and hypertension. All patients underwent coronary angiography followed by elective stenting. Clinical outcomes were assessed on average after 44 months of outpatient follow-up.Results. During the follow-up period, 43% of patients retained class III angina; the decrease in systolic (SBP) and diastolic blood pressure (DBP) was 18and 14-mm Hg, respectively. There were 35 cases of myocardial infarction (MI) in this category of subjects. We revealed that 57% of patients had a progression of angina: from class III to class IV; the decrease in SBP and DBP was 10and 18-mm Hg, respectively. There were 110 cases of MI and 10 cases of acute cerebrovascular accident in these patients.Conclusion. Inadequate control of SBP in patients after stenting due to stable exertional angina leads to a greater number of complications, mainly myocardial infarction.